Microteaching Practice and Educational Field Experiences: The Impact on the Professional Performance of Prospective Teachers - Dina Ramadhanti; Diyan Permata Yanda (IJECA (International Journal of Education and Curriculum Application), 2025)
Microteaching practices and educational field experiences have long been part of the professional training of teachers. Both are requirements that must be taken by prospective teachers to become skilled and professional teachers. This study aims to describe the effect of microteaching practices and educational field experiences on the professionalism of prospective teachers. A quantitative approach with the correlational method was used to analyze the data obtained from 178 teacher candidates who took part in the practice of microteaching and carried out 6 months of educational field experience. The instrument used to collect data is a questionnaire. The results of the data analysis show that the microteaching practice and educational field experiences affect the professionalism of prospective teachers. However, educational field experiences have a more dominant influence than the practice of microteaching. Educational field experience directly shapes the character of prospective teachers to become professional educators because they are faced with real experience in the field. Meanwhile, the practice of microteaching occurs in a limited space so the teaching experience gained by prospective teachers is also limited. More effective management of microteaching practices needs to be a concern because through microteaching prospective teachers theoretically and practically gain knowledge about basic teaching skills and skills in compiling learning tools. The knowledge gained during the practice of microteaching is used by prospective teachers while carrying out educational field experiences.